PEMANFAATAN EKSTRAK ETANOL BIJI BUAH DELIMA SEBAGAI ANTI KANKER LIDAH SP-C1 - Mahmud Kholifa (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Tongue cancer has invasion characteristic and metastatic that high to regional lymph nodes or distant. Cancer treatment is categorized as a disease that difficult to cure despite a holistic therapy, are still at risk of secondary cancers arise, so a new strategy is needed to use cheaper and safer materials namely herbal ingredients, one of which with ethanol extract of pomegranate seeds. The purpose of this study was to test ability concentration of ethanol extract of pomegranate seeds as anti-cancer and determine the appropriate dosage for humans. The method used with detect cells undergoing apoptosis with staining ethidum bromide and acridine orange and measure the diameter of cancers in nude mice after treatment with ethanol extract of pomegranate seeds. Results are expected for the first year of the discovery of new anti-cancer from herbal ingredients, especially ethanol extract of pomegranate seeds. While the outcome for the second year was the discovery of anti-cancer dose corresponding to a human from the ethanol extract of pomegranate seeds. In conclusion, the concentration of ethanol extract of pomegranate seeds influential as an anti - cancer on cultured human tongue squamous cell carcinoma and the increases of concentration of ethanol extract of pomegranate seeds followed by the increases of percentage apoptosis on cultured human tongue squamous cell carcinoma.Keywords : tongue cancer, anti-cancer, apoptosis, ethanol extract of pomegranate seeds, herbal ingredients.